The Effect of Moringa Leaf Extract (moringa oleifera) on the Microscopic Structure of the Lungs of Male Wistar Rats Given Inhalation of E-cigarette Liquid Vapor - Bialangi, Alif Akbar; Ismail, Akhmad; Purnawati, Ratna Damma; Mundhofir, Farmaditya Eka Putra (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Moringa leaf extract is proven to have high antioxidant bioactive compounds and acts as an anti-inflammatory and prevents cell damage due to exposure to free radicals or oxidative. In the respiratory system exposed to Electronic Delivery Nicotine System liquid vapor, an inflammatory response and oxidative stress occur. Objective: This study aimed to determine the effect of Moringa leaf extract (Moringa oleifera) on the microscopic structure of the lungs of male Wistar rats given inhalation of e-cigarette liquid vapor. Methods: This research is an experimental laboratory with Post Test Only Control Group Design. Rats were divided into 4 groups containing 6 rats in each group, determined based on simple random sampling with the following divisions: Aquadest 3 mL (K1), gave inhalation of liquid vapours of electric cigarettes (K2), gave inhalation of liquid vapours of electric cigarettes + Moringa leaf extract with the dekoxy method dose of 500 mg/kgBW (P1), administration of vapor inhalation of e-cigarette liquid + Moringa leaf extract with the dekoxy method at a dose of 500 mg/kgBW (P2). Termination of the experimental animals was carried out on the 15th day and the rat pulmonary organs were taken to assess the microscopic structure of the rat lung. Results: The results of the Kruskal-Wallis test and continued with the Mann-Whitney test showed a significant difference (p < 0.05), however, there was no significant difference in the degree of pulmonary damage in the P1 to P2 groups. Conclusion: There is an effect of Moringa leaf extract (Moringa oleifera) on the microscopic structure of the lungs of male Wistar rats given inhalation of liquid vapor of electric cigarettes.